Assessment of Coliform Bacteria as Indicator of Water Quality in Jigawa State Nigeria - Lawan, Naima Suleiman; Yakubu, Abdulhadi; Abdulsalam, Zainab Jamil; Zandam, Nuhu Danladi (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Groundwater is sometimes considered as the cleanest form of water available to Nigerians. A total of two hundred water samples (10 from each of the 20 cities) were analyzed for the presence of coliform bacteria as an indicator of water quality. The mean coliform viable counts, aerobic mesophilic bacterial count as well as a biochemical test were conducted. Based on the result obtained, seven cities were found to contain coliform count above the acceptable limit of the World Health Organization (WHO) for drinking water. Escherichia coli was also found in water samples of four cities. Presence of faecal coliform is an indication of faecal contamination of any drinking water which can be due to leakage of pipes from the main source. Efforts need to be intensified in the monitoring of activities in this rapidly expanding industry with a view to raising standards.